The RHD gene is highly detectable in RhD-negative Japanese donors. - Okuda, H (1997)
Recent molecular studies on the Rh blood group system have shown that the Rh locus of each haploid RhD-positive chromosome is composed of two structural genes: RHD and RHCE, whereas the locus is made of a single gene (RHCE) on each haploid RhD-negative chromosome. We analyzed the presence or absence of the RHD gene in 130 Japanese RhD-negative donors using the PCR method. The RhD-negative phenotypes consisted of 34 ccEe, 27 ccee, 17 ccEE, 26 Ccee, 19 CcEe, 1 CcEE, and 6 CCee. Among them, 36 (27.7%) donors demonstrated the presence of the RHD gene. Others showed gross or partial deletions of the RHD gene. These results were confirmed by Southern blot analysis. Additionally, the RHD gene detected in the RhD-negative donors seemed to be intact through sequencing of the RhD polypeptide cDNA and the promoter region of RHD gene. The phenotypes of these donors with the RHD gene were CC or Cc, but not cc. It suggested that there is some relationship between the RHD gene and the RhC phenotypes in RhD-negative individuals. In Caucasian RhD-negative individuals, the RHD gene has not been found outside of the report of Hyland et al. (Hyland, C.A., L.C. Wolter, and A. Saul. 1994. Blood. 84:321-324). The discrepant data on the RHD gene in RhD-negative donors between Japanese and Caucasians appear to be derived from the difference of the frequency of RhD-negative and RhC-positive phenotypes. Careful attention is necessary for clinicians in applying RhD genotyping to clinical medicine.